Acceptability of HIV prevention information delivered through established geosocial networking mobile applications to men who have sex with men - Czarny, Heather N. (AIDS Behav, 2017)
Geosocial networking (GSN) applications could disseminate HIV prevention information to thousands of men who have sex with men (MSM); however, acceptability of the type of information, methods, and frequency of information delivery are unknown. Acceptability of these constructs were assessed through a survey of 224 MSM at the Milwaukee Pridefest. All types of information were found acceptable. A sexual health section and self-seeking information were the most acceptable method and frequency of delivery. Demographics and differences in app usage did not correlate to acceptability. Continued research focusing on the feasibility of incorporating HIV prevention information into GSN applications is needed.